Bordetella petrii recovered from chronic pansinusitis in an adult with cystic fibrosis. Issue 4 (2015) - Biederman, Laura; Rosen, Marc R.; Bobik, Brent S.; Roberts, Amity L.
Abstract: To date Bordetella petrii has infrequently been identified within the clinical setting likely due to the asaccharolytic nature of this organism. We present a case of B. petrii recovered on two separate events in a patient with adult cystic fibrosis experiencing chronic pansinusitis.